Challenges in assessing population reach in a pragmatic trial - Beverly B. Green; William M. Vollmer; Erin Keast; Amanda F. Petrik; Gloria D. Coronado (Preventive Medicine Reports, 2019)
Strategies and Opportunities to STOP Colon Cancer in Priority Populations (STOP CRC) was a pragmatic cluster-randomized trial conducted at federally qualified health centers and designed to “Reach” as many unscreened patients as possible by directly mailing them fecal screening tests.STOP CRC used an electronic health record registry to identify individuals' needing CRC screening and mail interventions to them. The registry was updated daily removing individuals completing CRC screening or those who no longer were clinic patients. Reach, a component RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance), is defined as the absolute number, percent, and representativeness of individuals “willing to participate in” or “exposed to” an initiative. We describe the complexities of measuring Reach in a pragmatic trial.Overall 21,134 patients were on the registry list for at least one day, with 18,226 remaining after removing patients completing screening before any mailings. Observed Reached (the percent of individuals exposed to the intervention) using each denominator was 30.7% and 35.6% respectively. Reach improved only modestly after accounting for factors that made it impossible for clinics to send mailings. Few differences were observed in demographic and health care utilization factors among individuals Reached versus not Reached, suggesting that health center Implementation was more influential than patients' willingness or ability to participate.A pragmatic definition of Reach that accounted for dynamic changes the absolute number eligible and the proportion exposed was more useful than traditional definitions of Reach. Actual Reach was dependent on Implementation and not patient level characteristics.Clinical Trials Registration Number: ClincalTrials.gov (NCT01742065).